Public Procurement Regulation in Bangladesh: A Preliminary Analysis - Hoque, Ridwanul (Journal of Malaysian and Comparative Law, 2019)
Bangladesh’s public procurement law has sought to ensure transparency, accountability and fairness in government procurements. Whether its accountability-goal has been satisfactorily achieved is, however, a debatable issue. I will argue that the procurement rules are somewhat de-effected both by bureaucratisation and technical avoidance of the rules. On the other hand, the judiciary does not follow a robust review of public contracts. With this background in mind, I will analyse the Bangladeshi procurement laws and practices with a view to fathom ‘accountability’ in public procurements. I conclude by urging for simplified rules, more circumscribed administrative discretion, and a robust but principled judicial review of procurement decisions. This has been a theoretical study, based on primary and secondary sources of knowledge.